National Responses to Global Concern: Examination of Disaster Management in Türkiye from the Perspective of Environment, Security and Sustainable Development - Aliyev, Pelin; Demirbilek, Burcin; Kose, Zeynep; Köse, Zeynep; Aliyev, Pelin (Afet ve Acil Durum Yonetimi Baskanligi (AFAD))
While climate change-induced natural disasters are increasing in number, their destructive effects are also becoming more severe. This study answers the question whether disaster management policies in Türkiye are in line with the ‘2030 Agenda for Sustainable Development’ and the ‘Sendai Framework for Disaster Risk Reduction (2015-2030)’. Within the scope of the research, Türkiye’s Twelfth Development Plan and AFAD Strategic Plan 2024-2028 are analysed and a comparison is made in the context of the Sendai Framework for Disaster Risk Reduction. Accordingly, it is determined that climate change is a global concern and a security issue due to the disasters it causes and negatively affects sustainable development; the current disaster management approach in Türkiye is compatible with sustainable development goals and Sendai Framework for Disaster Risk Reduction (2015-2030); and finally, Türkiye’s disaster management is based on a multi-actor process and has a disaster governance approach. Content of this journal is licensed under a Creative Commons Attribution 4.0 International Non-Commercial License
Keywords: Disaster management; Environmental security; Climate change; Sustainable development; Türkiye